An Overview of Anemia Cases Among Third Trimester Pregnant Women at Puskesmas Tegalrejo, Yogyakarta - Aini, Safira Nurul; Rokhanawati, Dewi (International Journal of Health Science and Technology, 2025)
Anemia remains a significant contributor to the rising maternal mortality rate (MMR) in recent years. In the Special Region of Yogyakarta, the prevalence of anemia among pregnant women increased from 14.23% in 2017 to 16.5% in 2021. Previous studies have shown that anemia during pregnancy may result in adverse maternal and fetal outcomes, including fetal growth restriction, premature delivery, low birth weight, congenital anomalies, and elevated risks of neonatal and perinatal mortality. This study aims to analyze the relationship between maternal age, interpregnancy interval, and nutritional status based on Mid-Upper Arm Circumference (MUAC), and the case of anemia among third-trimester pregnant women at Puskesmas (Public Health Center) Tegalrejo, Yogyakarta. A retrospective case–control design was used, involving 86 pregnant women with anemia (cases) and 86 without anemia (controls). Statistical analysis showed significant associations between all three factors and the case of anemia. At a 0.05 significance level, 70 respondents (81.4%) were of high-risk maternal age (<20 years or >35 years) (p = 0.000; OR = 13.542; 95% CI: 6.508–28.179); 62 respondents (72.1%) had a short interpregnancy interval (<2 years) (p = 0.000; OR = 7.996; 95% CI: 4.046–15.802); and 56 respondents (65.1%) had Chronic Energy Deficiency (CED) indicated by a MUAC of <23.5 cm (p = 0.000; OR = 6.160; 95% CI: 3.157–12.020). These findings confirm that maternal age, short interpregnancy intervals, and poor nutritional status are significant determinants of anemia in the third trimester.